Strengthen Constitutional Court’s Decision as Political Legal Perspective in Legislative Branch : Penguatan Putusan Mahkamah Konstitusi sebagai Politik Hukum Legislatif - Aprilian Sumodiningrat (Jurnal Konstitusi, 2023)
The disobedience of the Constitutional Court’s decisions is founded in the law-making processes that contradict the decision. Those disobediences have been intentional in some cases. This paper aims to discuss reinforcing the implementation of the Constitutional Court decision, especially in law-making processes. There are two research questions: First, what is the urgency to emphasize the decision in law-making processes? Second, what is the solution to the disobedience of the decision? This research uses normative juridical research methods with a conceptual approach to analyze those issues. This study provides: first, the obstacles to enforcing the Constitutional Court decision and strengthens the decision to bond the legislative branch. Second, the solution to the disobedience phenomenon is also interpreted as a commitment to encourage awareness of the legislative branch. The other solution is to put the constitutional court’s decision in the Law Making Act as one of the considerations in the law-making process.